PENGARUH METODE PEMBELAJARAN LEARNING START WITH A QUESTION (LSQ) TERHADAP HASIL BELAJAR IPS KELAS IV MIN 2 BANDAR LAMPUNG TAHUN PELAJARAN 2017/2018 - AFANDI, MUHAMMAD; NURJANAH, ISNAINI (TERAMPIL: Jurnal Pendidikan dan Pembelajaran Dasar, 2018)
Problems in this research is still low learning result of IPS student of class VI MIN 2 Bandar Lampung. Implementation of learning method of learning with a question (LSQ) aims to determine whether there is influence of Learning start with a question (LSQ) method to the learning result of IPS class IV in MIN 2 Bandar Lampung Lesson year 2017/2018.Type of research used is Quantitative research with quasy experimental method with nonequivalent control group design design. The location of the research was conducted at MIN 2 Bandar Lampung. Subjects in the study were students grade IV A and IV B MIN 2 Bandar Lampung as many as 69 students. Data collection methods used are Tests and documentation. The data analysis technique used is t-test. The test results show the average score of 34 students in the experimental class is 72.35 and in the control class of 35 students the average score is 66,57.Based on the results of hypothesis testing using Independent t-test obtained that the value of Sig = 0.001 or tcount = 3.627> ttable = 1.997, This means that the value of tcount is greater than the value of ttable both at the level of 5%. (0.001 <0.05). So it can be concluded that there is a significant influence on the application of learning learning method with a question to the learning outcomes of IPS students in grade IV MIN 2 Bandar Lampung in the academic year 2017/2018.